Mutants as Patches: Towards a formal approach to Mutation Testing - Lewowski Tomasz; Madeyski Lech (Foundations of Computing and Decision Sciences, 2019)
Background: Mutation testing is a widely explored technique used to evaluate the quality of software tests, but little attention has been given to its mathematical foundations.